The effect of harmonic exercises with auxiliary tools in developing some basic skills of tennis players. (Journal of the College of Basic Education, 2023)
The aim of the research is to prepare harmonic exercises using auxiliary tools and their impact on developing the effectiveness of some basic skills in tennis. And to identify the best group between the two research groups (experimental and control). The researcher used the experimental method with the two equal groups (the tight control) with the pre and posttest for its relevance to the nature of the research. The research community was determined by a deliberate method, and they are the players of the Iraqi Central Tennis Federation for the 2022 season, and their number is (27) players and their ages are from (14-15) years. The researcher chose the research sample in a random way, the experimental group, which numbered (11) players, and the control group, which numbered (11) players. The researcher prepared harmonic exercises with auxiliary tools that were implemented in the training units within (30) training units during (12) weeks and at a rate of (3) units per week, and after implementing the exercises and conducting the pre and posttest. The researcher concluded the ability of harmonic exercises in developing the effectiveness of the skill performance of the forehand and backhand skills in tennis and for the benefit of the experimental research group. And the use of auxiliary tools (the power base device) in developing the effectiveness of the skill performance of the forehand and backhand tennis skills. The researcher recommends the use of auxiliary tools (the power base device) in developing basic tennis skills because of their great role in developing skill performance. The necessity of using harmonic exercises in developing the effectiveness of the skill performance of the forehand and backhand skills in tennis.